2017
DOI: 10.1016/j.adolescence.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of online images on self‐harm: A qualitative study of young people aged 16–24

Abstract: To date, research on the role of the Internet in self-harm has focused on young people's interaction via the medium of text, with limited consideration of the effect of images. This qualitative study explores how young people understand and use online images of self-harm. Semi-structured interviews were conducted with a community sample of 21 individuals aged 16–24 living in Wales, UK, with a previous history of self-harm. Interviewees reported the role of the Internet in normalising young people's self-harm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(111 citation statements)
references
References 37 publications
(68 reference statements)
3
93
0
8
Order By: Relevance
“…However, for the purposes of this paper, we use the term self-harm to refer only to 'direct' harmful activities. Digital self-harm activities have emerged even in very general studies of adolescents' online behaviour [51] and in studies of other mental health conditions (e.g., depression [2], eating disorder [50]), however a small number of researchers have explicitly focused on online representations of self-harm [13,22,26,23,31,36,40,41,56,70]. For a review of studies relating to social media use for the discussion of self-harm and viewing of associated content (1998-2014), see Dyson et al [22].…”
Section: Studies Of Online Behaviourmentioning
confidence: 99%
“…However, for the purposes of this paper, we use the term self-harm to refer only to 'direct' harmful activities. Digital self-harm activities have emerged even in very general studies of adolescents' online behaviour [51] and in studies of other mental health conditions (e.g., depression [2], eating disorder [50]), however a small number of researchers have explicitly focused on online representations of self-harm [13,22,26,23,31,36,40,41,56,70]. For a review of studies relating to social media use for the discussion of self-harm and viewing of associated content (1998-2014), see Dyson et al [22].…”
Section: Studies Of Online Behaviourmentioning
confidence: 99%
“…Compared to other social media, Instagram was found to host the greatest proportion of visual self-harm content [42]. This is relevant because previous research has suggested that imagery and visual content may have greater impact on users than text, it is more appealing, attracts more attention and may have greater triggering potential [45,49]. We found that self-harm content on Instagram elicits high levels of audience engagement, especially the more graphic and explicit it is [37,39].…”
Section: Discussionmentioning
confidence: 58%
“…Finally, images and videos are increasingly frequent in SNs (Marchant et al, ). Online images and videos of self‐harm seem to facilitate reproduction of these behaviors, at least among the young (Jacob, Evans, & Scourfield, ). This kind of content provide relevant information that requires the development of new automatic methods to be processed in search of suicidal indicators.…”
Section: Resultsmentioning
confidence: 99%